Fracture Toughness and Elastic Modulus of Epoxy-Based Nanocomposites with Dopamine-Modified Nano-Fillers - Koh, Kwang Liang (2018)
This paper examines the effect of surface treatment and filler shape factor on the fracture toughness and elastic modulus of epoxy-based nanocomposite. Two forms of nanofillers, polydopamine-coated montmorillonite clay (D-clay) and polydopamine-coated carbon nanofibres (D-CNF) were investigated. It was found that Young’s modulus increases with increasing D-clay and D-CNF loading. However, the fracture toughness decreases with increased D-clay loading but increases with increased D-CNF loading. Explanations have been provided with the aid of fractographic analysis using electron microscope observations of the crack-filler interactions. Fractographic analysis suggests that although polydopamine provides a strong adhesion between the fillers and the matrix, leading to enhanced elastic stiffness, the enhancement prohibits energy release via secondary cracking, resulting in a decrease in fracture toughness. In contrast, 1D fibre is effective in increasing the energy dissipation during fracture through crack deflection, fibre debonding, fibre break, and pull-out.